Vein of Galen Malformations: The Texas Children's Hospital Experience in the Modern Endovascular Era. Issue 3 (21st May 2019) - Wagner, Kathryn M; Ghali, Michael G Z; Srinivasan, Visish M; Lam, Sandi; Johnson, Jeremiah; Chen, Stephen; Kan, Peter
Abstract: BACKGROUND: Vein of Galen malformations (VOGM) comprise nearly a third of pediatric cerebrovascular anomalies, with potentially devastating neurological and systemic complications. Advances in endovascular therapies have dramatically improved outcomes compared to historical surgical treatments, and neurosurgeons are an essential component of the multidisciplinary critical care team. OBJECTIVE: To retrospectively review pediatric patients with VOGM treated at Texas Children's Hospital (TCH), a quaternary referral center, over 15 yr, and present lessons learned in treating children with modern endovascular techniques. METHODS: Charts from TCH were retrospectively reviewed for the past 15 yr. Patients with diagnosis including "Vein of Galen, " "Vein of Galen malformation, " "Vein of Galen aneurysmal malformation, " or any abbreviations (ie, VOG, VOGM, VOGAM) were reviewed. Presentation, imaging, treatment specifics, and clinical outcomes were reported. RESULTS: There were 18 patients with VOGM managed at TCH from 2002 to 2018 with a total of 29 embolizations. Seventeen were performed with a single embolisate (NBCA or Onyx), and 12 with a combination. A dual lumen balloon catheter was used as an adjunct in 3 embolizations. Complications occurred in 5 embolizations (24%), including hemorrhage, embolisate migration, and femoral vessel occlusion. Surviving patients were followed for a mean of 38 mo, with 12 having normal or near-normal neurological development. CONCLUSION: VOGM can present with a myriad of neurological and systemic symptoms, potentially in extremis. Neurosurgical involvement in these cases is critical, as urgent treatment can be lifesaving. Patients may require multiple treatment sessions using a variety of endovascular tools and techniques.